Presumptive red maple leaf toxicosis in a horse - D, Kang; R, Neto; L, Henker; T, Lunardon (Brazilian Journal of Veterinary Pathology, 2023)
Clinical History: A 16-year-old Quarter Horse gelding was presented for a 3-day history of lethargy, marked anemia, cyanotic oral mucous membrane, delayed jugular refill, and dark red urine, which retained the discoloration after centrifugation. Relevant in-house laboratory findings included packed cell volume of 15.3% [reference interval (RI): 32.0-48.0], elevated mean corpuscular hemoglobin concentration (MCHC) (61.1 g/dL; RI: 31.0-37.0), and a high hemolysis index (1642; RI: 0-43). Blood smears revealed moderate amounts of ghost cells (Fig 1, arrows) and eccentrocytes (Fig 1, arrowheads) within a highly hemolytic background.